Body Composition of Competitive Bodybuilders: A Systematic Review of Published Data and Recommendations for Future Work. Issue 3 (18th March 2023) - Bauer, Pascal; Majisik, Alan; Mitter, Benedikt; Csapo, Robert; Tschan, Harald; Hume, Patria; Martínez-Rodríguez, Alejandro; Makivic, Bojan
Abstract: Bauer, P, Majisik, A, Mitter, B, Csapo, R, Tschan, H, Hume, P, Martínez-Rodríguez, A, and Makivic, B. Body composition of competitive bodybuilders: a systematic review of published data and recommendations for future work. J Strength Cond Res 37(3): 726–732, 2023—The purpose of this review was to systematically summarize studies measuring the body composition of competitive bodybuilding athletes to provide recommended values for preparation and during competition. The protocol was preregistered with PROSPERO (CRD42020197921) and followed the guidelines of the Preferred Reported Items for Systematic Reviews and Meta-Analysis. A search of 5 electronic databases (PubMed, Web of Science, SportDiscus, CINAHL, and Scopus) was conducted to retrieve all relevant publications from January 1, 2000, up to June 13, 2021. Of 16 studies meeting the inclusion criteria, 6 presented longitudinal data on competition preparation and were discussed in detail. In the general preparation phase, body fat levels of bodybuilding athletes ranged between 15.3 and 25.2% (female) and from 9.6 to 16.3% (male). Close to competition, however, body fat levels were substantially lower, ranging from 8.1 to 18.3% for female and 5.8–10.7% for male athletes. All studies comparing relative body fat values at various time points during competition preparation found significant reductions between 30 and 60% in relative body fat, whereas lean mass was mostly maintained. Findings from the studies included in this review suggest that most bodybuilding competitors keep resistance training volume high while increasing aerobic training volume when preparing for competition. Findings on energy intake and macronutrient distribution were unclear and should be addressed in future studies. Further research, especially on contest preparation, is warranted and should include more details about training programs, nutritional strategies, psychosocial situation, anabolic androgen steroid, and supplement use as well as measurement protocols and preparation.